Optimum Conditions for Extraction of Antibacterial Compounds from Citrus Aurantifolia Fruit Peel Waste - Rima Munawaroh (Pharmacon: Jurnal Farmasi Indonesia, 2017)
Citrus fruit peel is a major waste in citrus fruit processing industry. The research on extraction activecompounds of Citrus aurantifolia (lime) fruit peel waste and antibacterial activity assay has been done. Theaim of research was to get optimum condition to extract their active compounds which have antibacterialactivity. The dried lime fruit peel was extracted by maceration method using ethanol 48%, 72%, and 96%.The dried and fresh lime fruit peel were also extracted using ethyl acetate. Antibacterial assay was done bydiffusion agar against Staphylococcus aureus ATCC 25923 and Escherichia coli ATCC 25922. The resultshowed that optimal condition to extract antibacterial compound using fresh sample with ethyl acetate assolvent. The ethyl acetate extract of fresh sample was more active against S. aureus than E. coli.